Treatment of Hyperlactatemia in Acute Circulatory Failure Based on CO2-O2-Derived Indices: Study Protocol for a Prospective, Multicentric, Single, Blind, Randomized, Superiority Study (The LACTEL Study) - Caruso, Vincenza; Besch, Guillaume; Nguyen, Maxime; Pili-Floury, Sebastien; Bouhemad, Belaid; Guinot, Pierre-Grégoire, the Lactel Study Group; Martin, Audrey; Radhouani, Mohamed; Constandache, Tiberiu; Grosjean, Sandrine; Voizeux, Pierre; et al. (Frontiers in Cardiovascular Medicine, 2022)
Hyperlactatemia is a biological marker of tissue hypoperfusion with well-known diagnostic, prognostic and therapeutic implications in shock states. In daily clinical practice, it is difficult to find out the exact mechanism underlying hyperlactatemia. Central Venous-to-Arterial CO2 difference (pCO2 gap) is a better parameter of tissue hypoperfusion compared to the usual ones (clinical examination, venous saturation). Furthermore, the ratio between the pCO2 gap and the arterial-venous oxygen differences p(v−a)CO2 / C(a−v)O2 may be a promising indicator of anaerobic metabolism, allowing to identify different causes of tissue hypoxia, thus hyperlactatemia. The main study aim is to demonstrate that early hemodynamic resuscitation based on an algorithm integrating the pCO2 gap and p(v−a)CO2 / C(a−v)O2 ratio versus usual clinical practice in acute circulatory failure improve lactate clearance.